Inclusive Open Education: Instructional Design of an E-book - Tenorio-Sepúlveda, Gloria Concepción; Muñoz-Ortiz, Katherine del Pilar; Nova-Nova, Cristóbal Andrés (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Fostering inclusive open education is everyone’s responsibility. The instructional design of an electronic book for the development of information and digital literacy skills is presented. It is focused on people with visual impairment. The ADDIE model and the principles of Universal Design for Learning are used. A roadmap was made to define initial aspects. As future work, the book will be developed and shared as an open educational resource with Creative Commons BY-SA license to encourage its reuse. It is suggested to measure the development of other competencies based on its use.